Digital Light Processing 3D Printing of Tough Supramolecular Hydrogels with Sophisticated Architectures as Impact‐Absorption Elements (Adv. Mater. 34/2022). Issue 34 (25th August 2022) - Dong, Min; Han, Ying; Hao, Xing Peng; Yu, Hai Chao; Yin, Jun; Du, Miao; Zheng, Qiang; Wu, Zi Liang
Abstract : Printed Tough Hydrogels In article number 2204333, Zi Liang Wu and co‐workers demonstrate Digital Light Processing 3D printing of supramolecular hydrogels into sophisticated architectures with "bottom‐up" projection approach. Fast gelation and toughening are realized during the printing by in situ formation of coordination complexes as physical crosslinks of the gel matrix, enabling high‐efficiency processing of tough hydrogels as structural elements.